If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1(3x + -12) = 0 Reorder the terms: 2x + -1(-12 + 3x) = 0 2x + (-12 * -1 + 3x * -1) = 0 2x + (12 + -3x) = 0 Reorder the terms: 12 + 2x + -3x = 0 Combine like terms: 2x + -3x = -1x 12 + -1x = 0 Solving 12 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 0 + -12 -1x = 0 + -12 Combine like terms: 0 + -12 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| 16x+9=8x+42 | | 27-2-4-(-k-3)=-16-(3k-4) | | (x+20.6)*0.604+(125-12.5-2.06-0.1*x)*0.471=150 | | 4.68x+1=21.9024+x | | g-16/4 | | 2x+12+6x+16= | | -x-29=13+2 | | 4x^2+3x=2 | | 15m-19m=16 | | 6/7x-5/7=8 | | (z-1)(z-7)=0 | | 3x-5(-2x-8)+4=2-(x-4) | | (x+20.6)*0.604+(65-6.5-0.1*x-2.06)*0.471=130 | | (4v+6)(2+v)=0 | | 8x+5=14+11x | | -5+(-3) = | | 15x+4y=25 | | 5x^9-40x^7= | | 4(u-5)(-u+2)=0 | | (w+7)(w+2)=0 | | 50+20x=18 | | 25w^6+35w^3=0 | | (x+20.6)*0.604+(65-6.5-0.1*x-2.06)*0.471=150 | | -7(x-2)-3(4-x)=22 | | 2x+186=10x-6 | | 6x^3+3x^2+8x+4= | | 72+x+(x+2)=360 | | 31-4x=5x+15 | | 33-(2c+3)=2(c+5)+c | | x^2+13+6x-4=-3x-9 | | 6-3i/5-6i | | 4k-8/24-12k |